Interfacial engineering of tungstic disulfide–carbide heterojunction for high-current-density hydrogen evolution. Issue 42 (26th September 2022) - Wang, TaiKun; Hong, Zhaoan; Sun, Fapeng; Wang, Bicheng; Jian, Chuanyong; Liu, Wei
Abstract : We report the large-area tungstic disulfide–carbide (WS2 –WC) heterojunction with abundant interfaces grown on W substrates via a facile solid-state synthesis method. Abstract : Developing low-cost and high-efficiency electrocatalysts to electrolyze water is an effective method for large-scale hydrogen production. For large-scale commercial applications, it is crucial to call for more efficient electrocatalysts with high-current density (≥1000 mA cm −2 ). However, it is challenging to simultaneously promote the large-scale production and hydrogen evolution reaction (HER) activity of these hydrogen catalysts. Herein, we report the large area tungstic disulfide–carbide (W/WS2 –WC) heterojunction electrode vertically grown on an industrial-grade tungsten substrate by the solid-state synthesis method. The W/WS2 –WC heterojunction electrode achieves a low overpotential of 473 mV at 1000 mA cm −2 in alkaline electrolytes.